The Winner by a Nose: Intranasal Midazolam. Issue 5 (September 2019) - Faught, Edward
Safety and Efficacy of Midazolam Nasal Spray in the Outpatient Treatment of Patients With Seizure Clusters—A Randomized, Double-Blind, Placebo-Controlled Trial. Detyniecki K, Van Ess PJ, Sequeira DJ, Wheless JW, Meng TC, Pullmnaan WE. Epilepsia . 2019. doi:10.1111/epi.15159 . Epub ahead of print. Objective: To evaluate the safety and efficacy of a novel formulation of midazolam administered as a single-dose nasal spray (MDZ-NS) in the outpatient treatment of patients experiencing seizure clusters (SCs). Methods: This was a phase III, randomized, double-blind, placebo-controlled trial (ClinicalTrials.gov NCT01390220) with patients aged ≥12 years on a stable regimen of antiepileptic drugs. Following an in-clinic test dose phase (TDP), patients entered an outpatient comparative phase (CP) and were randomized (2:1) to receive double-blind MDZ-NS 5 mg or placebo nasal spray, administered by caregivers when they experienced an SC. The primary efficacy end point was treatment success (seizure termination within 10 minutes and no recurrence 10 minutes to 6 hours after trial drug administration). Secondary efficacy end points were proportion of patients with seizure recurrence 10 minutes to 4 hours and time to next seizure >10 minutes after double-blind drug administration. Safety was monitored throughout. Results: Of 292 patients administered a test dose, 262 patients were randomized and 201 received double-blind treatment for an SC (n = 134 MDZ-NS, n = 67 placebo, modified intent-to-treat population). A significantly greater proportion of MDZ-NS than placebo-treated patients achieved treatment success (53.7% vs 34.4%; P = .0109). Significantly, fewer MDZ-NS- than placebo-treated patients experienced seizure recurrence (38.1% vs 59.7%; P = .0043). Time-to-next seizure analysis showed early separation (within 30 minutes) between MDZ-NS and placebo that was maintained throughout the 24-hour observation period (21% difference at 24 hours; P = .0124). Sixteen (5.5%) patients discontinued because of a treatment-emergent adverse event (TEAE) during the TDP and none during the CP. During the CP, 27.6% and 22.4% of patients in the MDZ-NS and placebo groups, respectively, experienced ≥1 TEAE. Significance: The MDZ-NS was superior to placebo in providing rapid, sustained seizure control when administered to patients experiencing an SC in the outpatient setting and was associated with a favorable safety profile.